Stroke Rate vs Distance in Rowing - Kleshnev, V. (coachesinfo.com)
Regressions and prognostic SR and SD can be used for more accurate evaluation of the race and training parameters in any boat type; Analysis shows that gold medals were won by means of either higher SR or longer SD. However, this depends upon boat type. Sweep crews used the first way (SR) and scullers the second (SD); Significant differences were found between rowers of different countries in "SR vs. SD" accents; Modelling the "SR vs. SD" factor brings an idea that balanced or "longer SD" approaches are more preferable for increasing of boat speed than "higher SR" approach.